Tropical forager gastrophagy and its implications for extinct hominin diets. (February 2016) - Buck, Laura T.; Berbesque, J. Colette; Wood, Brian M.; Stringer, Chris B.
Abstract: Reconstruction of extinct hominin diets is currently a topic of much interest and debate, facilitated by new methods such as the analysis of dental calculus. It has been proposed, based on chemical analyses of calculus, that Neanderthals self-medicated, yet this conclusion has been questioned. Gastrophagy has been suggested as an alternative explanation for the Neanderthal data, based on ethnographic analogies, which show this practice to have been widespread in traditional extant Homo sapiens diets, and nutritional evidence for its benefits at high latitudes. Here we expand the discussion of the potential importance of gastrophagy in human evolution by considering its role for an extant group of tropical foragers, the Hadza of Tanzania, and questioning its role in the diets of extinct tropical hominin species. Gastrophagy is frequently practiced among the Hadza and adult men in particular consume substantial, seasonally variable, amounts of prey guts. In addition to the important fact that gastrophagy is not a rare event, this demographic information may be useful in interpreting evidence from archaeological samples. The consumption of semi-digested chyme would have allowed extinct hominins to gain calories from plant sources without the cost of digesting them, possibly contributing to the encephalisation and shrinking of the gut in genus Homo . As an easy to process food-source, chyme could have likewise been an important food source for the old and the young, potentially playing a part in reducing inter-birth intervals and increasing reproductive success in our lineage. Thus, gastrophagy may have played a key part in human evolution and its potentially confounding signal should be considered in future dietary reconstructions. Highlights: First explicit description of gastrophagy and its context in extant tropical foragers Discusses the potential importance of gastrophagy during the course of human evolution in Africa Discusses the potential for gastrophagy to confound palaeodietary reconstructions